Umbilical Cord Serum Erythropoietin Levels and Maternal Smoking in Pregnancy - Soner Sazak; Sinan Mahir Kayiran; Yahya Paksoy (The Scientific World Journal)
Objective. To evaluate the effect of maternal smoking during pregnancy on levels of umbilical cord erythropoietin. Methods. Erythropoietin levels were measured in umbilical cord sera of 60 newborns who were delivered vaginally at term. There were 20 (33%) smoking and 40 (67%) nonsmoking mothers. Results. Mean cord serum erythropoietin levels were significantly lower in the nonsmokers (nonsmokers, 24 ± 9 IU/L; smokers, 61 ± 46 IU/L; P<.001). There was a significant positive correlation between the number of cigarettes smoked per day and cord serum erythropoietin levels (r, 0.58; P≤.05). Conclusions. Smoking during pregnancy is associated with increased levels of umbilical cord erythropoietin at birth. This may indicate a risk of fetal hypoxia and growth restriction. Education and encouragement of cessation of smoking during pregnancy are important to avoid associated fetal and maternal morbidity and mortality.